1998
DOI: 10.1098/rspb.1998.0315
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet sexual dimorphism and assortative mating in blue tits

Abstract: In spite of strong evidence for viability-based sexual selection and sex ratio adjustments, the blue tit, Parus caeruleus, is regarded as nearly sexually monomorphic and no epigamic signals have been found. The plumage coloration has not, however, been studied in relation to bird vision, which extends to the UV-A waveband (320^400 nm). Using molecular sex determination and UV/VIS spectrometry, we report here that blue tits are sexually dichromatic in UV/blue spectral purity (chroma) of the brilliant crown patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
348
2
6

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(368 citation statements)
references
References 27 publications
10
348
2
6
Order By: Relevance
“…Consistent with these hypotheses for the maintenance of elaborate monomorphism, research has shown that elaborate traits are related to male and female mate preference (Jones and Hunter 1993;Arnold et al 2002;Hill 1993Hill , 2002Torres and Velando 2005), pairing success (Daunt et al 2003), reproductive success (Ruusila et al 2001;Massaro et al 2003), various measures of individual quality (phenotypic condition, Velando et al 2001;survival, Hõrak et al 2001; dominance, Kraaijeveld et al 2004), and to assortative pairing (Andersson et al 1998;Jawor et al 2003;Safran and McGraw 2004).…”
mentioning
confidence: 84%
“…Consistent with these hypotheses for the maintenance of elaborate monomorphism, research has shown that elaborate traits are related to male and female mate preference (Jones and Hunter 1993;Arnold et al 2002;Hill 1993Hill , 2002Torres and Velando 2005), pairing success (Daunt et al 2003), reproductive success (Ruusila et al 2001;Massaro et al 2003), various measures of individual quality (phenotypic condition, Velando et al 2001;survival, Hõrak et al 2001; dominance, Kraaijeveld et al 2004), and to assortative pairing (Andersson et al 1998;Jawor et al 2003;Safran and McGraw 2004).…”
mentioning
confidence: 84%
“…In addition to foraging, blue tits are dimorphic in the UV and seem to use these cues in mate choice (Andersson et al 1998;Hunt et al 1998). Furthermore, some of the light environments likely to be present in a blue tit's habitatö`woodland shade' (Endler 1993b) in particularömay be quite rich in short wavelength light.…”
Section: Discussionmentioning
confidence: 99%
“…focused on three hypotheses regarding the functional signi¢cance of avian UV vision: (i) mate choice, (ii) foraging, and (iii) navigation. To date, behavioural studies have provided evidence that UV cues play an important role in conspeci¢c signalling in several bird species (Maier 1993;Bennett et al 1996Bennett et al , 1997Andersson & Amundsen 1997;Hunt et al 1997Hunt et al , 1998Andersson et al 1998). Here, we focus on the hypothesis that UV vision enhances foraging.…”
Section: Introductionmentioning
confidence: 99%
“…This is in stark contrast with much of the previous work on the function of ornaments similarly expressed in males and females, which has shown that both males and females typically use shared ornaments in the same signalling contexts (reviewed in Amundsen & Pärn, 2006). This includes signals of quality that are assessed by potential mates of either sex (Andersson, Örnborg, & Andersson, 1998;Nolan et al, 2010;Torres & Velando, 2003) and signals of status that communicate fighting ability (Crowley & Magrath, 2004;Kraaijeveld et al, 2004;Viera, Nolan, Côté, Jouventin, & Groscolas, 2008). Likewise, the pattern that male and female ornaments function similarly has also been commonly documented among species in which females have a reduced version of the male-like trait (Amundsen, Forsgren, & Hansen, 1997;Hill, 2002;Jawor, Gray, Beall, & Breitwisch, 2004;Siefferman & Hill, 2005).…”
Section: Discussionmentioning
confidence: 99%